2014
DOI: 10.1021/la500972w
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated Fatty Acids Reduce the Barrier of Stratum Corneum Lipid Membranes by Enhancing the Formation of a Hexagonal Lateral Packing

Abstract: The effectiveness of the skin barrier underlies the outer layer of the skin: the stratum corneum (SC). However, in several skin diseases this barrier is impaired. In two inflammatory skin diseases, atopic eczema and Netherton syndrome, an increased level of monounsaturated fatty acids (MUFAs) has been observed as opposed to healthy skin. In the present study, we aimed to investigate the effect of MUFAs on the lipid organization and skin lipid barrier using an in vitro model membrane system, the stratum corneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 60 publications
1
67
0
Order By: Relevance
“…There are two proposed mechanisms of action of lipidic penetration enhancers: lipid fluidisation and lipid phase separation. The first one involves disruption of the highly ordered SC lipid matrix, thereby increasing the diffusion of drugs 22,25,73,74 and the second one proposes that the enhancer forms a separate domain within the lipid phase which acts as permeable defects of the skin barrier. 22,24,73,75 In our simulations we have not observed any lipid phase separation; in all the studies oils are found to be completely miscible with the ceramides.…”
Section: View Article Onlinementioning
confidence: 99%
“…There are two proposed mechanisms of action of lipidic penetration enhancers: lipid fluidisation and lipid phase separation. The first one involves disruption of the highly ordered SC lipid matrix, thereby increasing the diffusion of drugs 22,25,73,74 and the second one proposes that the enhancer forms a separate domain within the lipid phase which acts as permeable defects of the skin barrier. 22,24,73,75 In our simulations we have not observed any lipid phase separation; in all the studies oils are found to be completely miscible with the ceramides.…”
Section: View Article Onlinementioning
confidence: 99%
“…Only a hexagonal lateral packing was observed in the 2 nd and 3 rd generation outgrowths, similar to other epidermal and full thickness HSEs [12,[25][26][27]. The abundant formation of a hexagonal packing in culture may be explained by: a reduction in SC FFAs levels and in their chain lengths or by an increase in the relative levels of MUFAs [28].…”
Section: Discussionmentioning
confidence: 55%
“…In contrast to the lateral packing, the LPP repeat distance can be maintained in all three Ex-HSE generations. Studies using model lipid systems also suggest that increased levels of MUFAs mainly affects the lateral packing while the lamellar phases are not changed [28].…”
Section: Discussionmentioning
confidence: 99%
“…In short, SC was isolated from ex vivo ski or 3D epidermal equivalents and used in the diffusion set-up was described previously (Mojumdar et al , 2014) using 0.34 mg/ml hydrocortisone in acetate buffer (pH 5.0) as diffusion fluid with 2–2,5 ml/hour flow speed. Samples were collected for a period of 15 hours, with a sampling time of 60 minutes.…”
Section: Methodsmentioning
confidence: 99%